Hasil Padi dan Kelimpahan Gulma dengan Aplikasi Jenis Pupuk Berbeda di Lahan Kering Tadah Hujan pada Musim Kemarau - Yugi Rahayu Ahadiyat; Sisno Sisno (Institut Pertanian Bogor, 2021)
Rice yield and proper weed control need to be increased through an environmentally friendly agricultural system approach in rainfed land during the dry season by reducing the dosage of synthetic fertilizers. This study aims to determine the effect of different fertilizer applications on rice yield and weed abundance in rainfed land during the dry season. The study used a split-plot design, with the main plot of rice variety, i.e., Situ Bagendit and IR-64, and subplots of fertilizer, namely synthetic fertilizers (N, P, K), organic fertilizers + P60 + ½ dose of synthetic fertilizers, organic fertilizers + PGPR + ½ dose of synthetic fertilizer and organic fertilizer + P60 + PGPR + ½ dose of synthetic fertilizer with three replications. The variables observed were rice yield components, namely panicle length, total empty grain and content per panicle, grain weights per hill, effective plot and hectare, 1000 grain weight, harvest index, and weeds summed dominance ratio (SDR). The synthetic fertilizers and three various organic fertilizers, biological fertilizers, and synthetic fertilizers gave different results on the SDR of weeds. The weeds of Sphenoclea zeynalica and Cyperus difformis showed consistent dominance with higher SDR than other weeds, i.e.,> 15 and > 10, respectively. The application of organic and biological fertilizers with half the recommended dosage of the synthetic fertilizers is equivalent to applying the recommended dosage of synthetic fertilizers on rice yield during the dry season on the rainfed dryland with low rainfall intensity and a low yield of 1.3–1.7 t/ha. Keywords: biological fertilizer, inorganic fertilizer, organic fertilizers, rice, weeds